Characteristics of woven carbon fabric current collector electrodes for structural battery. (15th January 2021) - Park, Hyun-Wook; Jang, Min-Su; Choi, Joo-Seung; Pyo, Jaechan; Kim, Chun-Gon
Graphical abstract: Abstract: The fourth industrial revolution has accelerated the demand for electricity-powered vehicles. Structural batteries with integrated structures and batteries offer a potential solution to this requirement. In this study, electrodes used in structural batteries were manufactured using a woven carbon fabric as the current collector. During the manufacturing process, Si rubber and an autoclave were used, and the influence of the electrode slurry thickness was studied. We confirmed that the electrode with a slurry thickness of 300 μ m had a relatively higher mechanical performance when applied as the electrode for structural batteries. The electrode showed the capacities of 112 mAhg −1 and 35–36 mAhg −1 at 0.1 and 10C, respectively. Additionally, the fabricated electrode showed a stable electrochemical reaction with high Coulombic efficiency throughout the 1C galvanostatic cycling and a capacity retention of 0.82 after the 500th cycle.